3-D magnetic graphene balls as sorbents for cleaning oil spills. (11th October 2019) - Tao, Tao; Li, Guangyao; He, Yanli; Yang, Xiufang
A 3-D magnetic graphene ball (MGB) material was prepared using cellulose as the carbon source. Carbon-encapsulated iron nanoparticles (CEINs) were first prepared by hydrothermal carbonization of cellulose powder at 180°C. Then, the prepared CEINs were catalytically graphitized to graphene-encapsulated iron nanoparticles (GEINs) at 900°C. Finally, GEINs were treated in carbon dioxide at 700°C, during which the iron core was oxidized to magnetite (Fe3 O4 ) nanoparticles, and graphene shells were peeled off from the iron cores to form graphene nanoplatelets. The graphene nanoplatelets consist of 1–10 layers graphene with the in-plane size of 20–30 nm. The prepared 3-D MGB was investigated for the removal of oil from water, which demonstrated outstanding adsorption performance and excellent recyclability.